Pivotal Suppliers and Market Power in Experimental Supply Function Competition - Jordi Brandts; Stanley S. Reynolds; Arthur Schram (Tinbergen Institute, 2011)
In the process of regulatory reform in the electric power industry, the mitigation of market power is one of the basic problems regulators have to deal with. We use experimental data to study the sources of market power with supply function competition, akin to the competition in wholesale electricity markets. An acute form of market power may arise if a supplier is pivotal; that is, if the supplier's capacity is required in order to meet demand. To be able to isolate the impact of demand and capacity conditions on market power, our treatments vary the distribution of demand levels as well as the amount and symmetry of the allocation of production capacity between different suppliers. We relate our results to a descriptive power index and to the predictions of two alternative models: a supply function equilibrium (SFE) model and a multi-unit auction (MUA) model. We find that pivotal suppliers do indeed exercise their market power in the experiments. We also find that observed behavior is consistent with the range of equilibria of the unrestricted SFE model and inconsistent with the unique equilibria of two refinements of the SFE model and of the MUA model.
Keywords: C92; D43; L11; L94; 330; Market Power; Electric Power Markets; Pivotal Suppliers; Experiments; Elektrizitätswirtschaft; Strompreis; Marktmacht; Unvollkommener Markt; Test